40Ar/39Ar ages of Precambrian manganese ore minerals from Sweden, India and Morocco - Lippolt, Hans J.; Hautmann, Siegfried (Mineralium deposita, 1995)
In order to test their chronometric potential, 40Ar/39Ar stepheating- (and 4He-) analyses have been carried out on five manganese ore minerals of the hollandite-cryptomelane series from three Precambrian manganese deposits (Ultevis/Sweden, Sitapar/India, Bachkoun/Morocco). Samples from the metamorphic occurrences Ultevis and Sitapar yielded Ar ages of 1.8 Ga and 0.95 Ga, interpreted as the age of postmetamorphic cooling (Hollandites/Ultevis) and of an early, K-introducing alteration process subsequent to amphibolite facies metamorphism (cryptomelanes/Sitapar). Both data are consistent with known chronologies of the “Svecokarelian” and “Satpura” orogenic cycles. A date of 670 Ma obtained for a hollandite from a volcanogenic vein deposit (Bachkoun), however, contrasts with published extrusion ages of 580-560 Ma for the volcanic host rocks (“Ouarzazate Series”), probably due to incorporation of excess argon. The use of the 40Ar/39Ar technique, together with multiple isotope systematics, made it nevertheless possible to establish a reasonable estimate of a mineralization age close to 580 Ma. Measurement of fractional Ar losses during vacuum step heating (500-1600 °C), although indicating good Ar retentivities, failed to define model diffusion parameters because of non-linear Arrhenius arrays. Helium diffusion results (200-1200 °C) indicated retention of radiogenic 4He by the samples, corroborated by U/He mineral dates between 0.96 and 0.31 Ga. Potassium-bearing manganese oxides are therefore able to retain argon (possibly also 4He) through geological times and may thus provide ages of ore-forming processes (and perhaps later cooling and alteration stages).
Im Titel sind die Zahlen 40 und 39 jeweils hochgestellt
Gesehen am 18.01.2023